An In Vitro Evaluation of the Effectiveness of Gotu Kola (Centella asiatica) on Inhibiting the Growth of Selected Microorganismsin Human Saliva - Alan N Talabani (College of Dentistry/ University of Baghdad, 2016)
Background: Gotu Kola (Centella asiatica) has been used as a traditional medicine for many years to cure different kinds of diseases. Studies have been reported that Gotu Kola extracts might be used as a cure for oral diseases such as periodontal disease. In the present study, Gotu Kola leaves extracted with water will be used to evaluate its effect on some microorganisms living in the human saliva using minimum inhibitory concentration (MIC) method. Material and Method:Gotu Kola fresh leaves extract have been used with water as a solvent, a rotary evaporator was used to separate the solvent from the extract. The following microorganisms: Streptococci, Lactobacilli, and Staphylococcus aureus have been isolated fromthe Saliva of ten volunteers participated in the present study. Nutrient broth tubes have been prepared for MIC test, where various concentrations of the Gotu Kola extracts (0.5mg/ml, 1 mg/ml, 2 mg/ml, 3 mg/ml, 4 mg/ml, and 5 mg/ml) were added, respectively. The tubes incubated at 370C for 48h. Results:The MIC test shows that a concentration of 4 mg/ml have the ability to inhibit the growth of oral Lactobacilli and 8 mg/ml has the ability to inhibit the growth of S. aureuswhich may be due to asiaticoside and asiatic acid which are active ingredients that the leaves extracts consists of. There was no MIC for Streptococci. Conclusion:The Gotu Kola leaves extract can be used to inhibit the growth of some oral microorganisms at certain concentration. Keywords:Centella asiatica, oral microorganisms, antimicrobial activity, minimum inhibitory concentration.